Conversion of CO2 on a highly active and stable Cu/FeOx/CeO2 catalyst: tuning catalytic performance by oxide-oxide interactions. Issue 14 (24th June 2019) - Lin, Lili; Yao, Siyu; Rui, Ning; Han, Lili; Zhang, Feng; Gerlak, Clifford A.; Liu, Zongyuan; Cen, Jiajie; Song, Liang; Senanayake, Sanjaya D.; Xin, Huolin L.; Chen, Jingguang G.; et al.
Abstract : Oxide–oxide interactions have been used to control textural properties and produce active and stable Cu/FeO x /CeO2 catalysts. Abstract : Nanoparticles of FeO x dispersed on ceria exhibit unique chemical and textural properties. They undergo a dynamic FeO x ↔ Fe transformation depending on the reaction conditions. The high density Fe oxide clusters dispersed over CeO2 are effective texture promoters that enhance the stability of Cu/CeO2 catalyst in the high temperature reverse water gas shift reaction. At the optimal Fe loading, the deactivation rate constant of a 5Cu1.6Fe/CeO2 catalyst is only 0.003 h −1, five times smaller than that of the monometallic 5Cu/CeO2 catalyst. In situ XRD, AP-XPS and XAFS characterizations reveal that the partially reduced Fe nanoparticles would be oxidized by CO2 in the reductive atmosphere and re-disperse into high density FeO x clusters under the high temperature CO2 hydrogenation process. The wetting phenomenon, maximizing the density of FeO x particles on the CeO2 support, benefits from strong oxide-oxide (Fe–O–Ce) interactions.